(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article is devoted to the formation of the resource base of private banks operating in the Republic of Uzbekistan. The data are taken from the analysis of financial statements on the banking system issued by the Central Bank of the Republic of Uzbekistan. It covers the activities of 6 existing private banks in the Republic of Uzbekistan. To solve the problem, we used the regression analysis and correlation method. In this case, we draw the appropriate conclusions using the method of regression and correlation analysis of the factors affecting the resource base of private banks. The study found that the volume of assets of private banks in the country (bank size), the number of branches, long-term interest rates, return on capital, and return on assets are positively linked to the resource base of private banks. In addition, a conclusion was drawn on the elimination of abstract problems in the formation of the resource base of private banks.